Penerapan Model Pembelajaran Problem-Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas VII pada Materi Bilangan - Widianti, Nyoman; Sari Purnamayanti, Ni Gusti Ayu Kadek; Kharisma Dewi, Ni Putu Dian; Bakkara, Bonica Nisra; Susilawati, Made (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to enhance the learning outcomes and engagement of grade VII students at SMP Negeri 5 Negara by implementing the Problem-Based Learning (PBL) model. PBL was chosen to address challenges in mathematics education, such as low student motivation and participation, by providing contextual and relevant learning experiences. The research employed a Classroom Action Research (CAR) approach, conducted over three cycles during the odd semester of the 2024/2025 academic year. The study involved 38 students as subjects, with data collected through tests and observations and analyzed using descriptive statistical methods with SPSS. The results showed a significant improvement in the students' average scores, increasing from 51.42 in Cycle I to 65.87 in Cycle II, and reaching 81.11 in the Post-test. Additionally, a decrease in standard deviation from 19.93 to 8.1 indicated more consistent learning outcomes. The proportion of students meeting the passing criteria also increased significantly across cycles, with nearly all students achieving success in the Post-test. These findings demonstrate that the PBL model is effective in improving students’ understanding of mathematical concepts while creating a more active, enjoyable, and effective learning environment to address challenges in mathematics education.